Estrategias De Intervención Para La Recuperación De Espacios Residuales En Los Bordes De Entornos Educativos - Suarez Sierra, Jonathan (Universidad Antonio Nariño, 2023)
This project is to design a booklet of intervention strategies for the recovery of residual spaces on the edges of educational environments. In which the 6 axes of intervention are managed and comply with each variable hand in hand with the minimum intervention criteria.